A research agenda for trust and distrust in a multilevel judicial system. Issue 3 (June 2022) - Popelier, Patricia; Glavina, Monika; Baldan, Federica; van Zimmeren, Esther
While public trust in the judicial system has been extensively explored in the US, this has been less common in Europe. The purpose of this paper is therefore to launch a research agenda on trust in courts. This is based on an overview of the empirical studies on trust/distrust in courts in Europe, which are assessed critically in light of the trust literature. We connect the concept of multilevel governance in which the EU operates to the concept of multilevel trust, which concerns the interrelations between interpersonal trust, interorganizational trust and system trust. Furthermore, we add structure to the existing literature on trust in and within courts in Europe by categorizing it into two main categories: (i) studies that focus on trust in courts within one (national or European) legal system and (ii) those that explore the interaction of trust in and between courts at different levels of governance (multilevel governance). We further examine whether different relational and institutional aspects of trust in courts, their drivers, dynamics and effect, as well as the recent trend of specialization in court systems have been sufficiently covered in the literature.